Demandas e dilemas da prática como componente curricular na formação de professores de biologia - Boton, Jaiane de Moraes (2019)
The successive changes regarding teacher training in Brazil, especially those occurring in the last decades, went through the “3+1” model, leading to the current proposition that is still being concluded, based on Law 9.394/96 (LDB), which includes curricular reconfigurations in undergraduate teacher training courses. It is important to highlight the role of the National Curricular Guidelines (DCN) for teacher training. Promulgated in 2002, these guidelines represent a set of principles, fundaments and procedures to be adopted in the institutional and curricular organization of educational institutions, and apply to all steps and modalities of basic education. This thesis is centered on the concept of Practice as Curricular Component (PCC), and has the objective to promote the articulation of different activities within an initial training course, with an interdisciplinary perspective. Considering the importance of this Practice for teacher training and the particularities of undergraduate courses for Biology teachers, our goals are to: (i) identify and discuss the plurality of the training of Biology teachers in Brazil; (ii) identify and discuss the different points of view regarding the training of Biology teachers; (iii) identify and discuss the different points of view regarding the PCC; and (iv) propose possible changes for the undergraduate courses for Biology teachers. To do so, we analyzed the curricular matrices of pedagogical projects from different undergraduate courses for Biology teachers, applied questionnaires to graduates from these courses and biology teachers working with basic education, and interviewed biology teacher trainers. For the analysis and treatment of the sampled data, we used content analysis. From this analysis, we observed that the majority of the courses is structured in accordance with the current legislation; there is a predominance of specific teaching subjects when compared to pedagogic teaching subjects; the PCC is applied in different manners and in different semesters within each course. About the individual subjects investigated (researchers, teacher trainers and teachers in training), we could observe a concern regarding the activities to be developed by the teachers in training in their future classrooms. These discussions mentioned the necessity of didactic-pedagogical knowledge, simulated classes, discussions and observations of classes. Furthermore, there is a general lack of knowledge regarding what is PCC, which is often confused with teacher internships and laboratory activities. We believe that a renewal of the teacher training courses is necessary, with special regards to the preservation of the specific characteristics of the teacher training courses. To achieve an improved university-school interaction, it is of the utmost importance that teacher training occurs as close as possible to the schools that they will attend.